1998
DOI: 10.1159/000024593
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Diffusive Samplers for the Measurement of Volatile Organic Compounds in the Indoor Air of 44 Homes in Southampton

Abstract: Diffusive sampling using tube-type adsorbent samplers can be applied to the measurement of volatile organic compounds (VOCs) in the air of homes and outdoors. In the present study samplers packed with Tenax TA have been used to investigate VOCs in the air of 44 homes and at 4 outdoor locations in the Southampton area of the UK as part of a study of the effects of measures for the alleviation of the symptoms of asthma. These measures included installation of mechanical ventilation with heat recovery (MVHR) syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Some of them have been frequently employed to quantify air pollutants or/and assess people's exposure to them. [21][22][23][24] However, these samplers are vulnerable to variations of environmental factors. [25][26][27][28] Tolnai et al compared the sampling rates (SRs) of Perkin-Elmer tube samplers and found there were up to 300% deviations in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have been frequently employed to quantify air pollutants or/and assess people's exposure to them. [21][22][23][24] However, these samplers are vulnerable to variations of environmental factors. [25][26][27][28] Tolnai et al compared the sampling rates (SRs) of Perkin-Elmer tube samplers and found there were up to 300% deviations in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…No quality-control details are given. Brown and Crump (1998) found D4 in 37.5 per cent of homes sampled in an investigation of volatile organic carbon compounds in indoor air samples from 44 homes in Southampton. The samples were collected using diffusive sampling over a four week period.…”
Section: Measured Environmental Concentrationsmentioning
confidence: 96%